1990
DOI: 10.1063/1.102653
|View full text |Cite
|
Sign up to set email alerts
|

Rapid thermal oxidation of GeSi strained layers

Abstract: The experimental results of the rapid thermal oxidation in the initial oxidation regime of molecular beam epitaxy grown GeSi strained layers are reported. It is shown that the dry oxidation rate of GeSi is the same as that of Si at different temperatures. After a very short initial time (∼10 s), the oxide thickness appears to be a linear function of time, which suggests that the kinetics of oxide growth during dry oxidation is limited by surface reaction controlled mechanisms. Further, the oxidation rate in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…ble gate (DG) metal-oxide-semiconductor field effect transistors (MOSFET) [1,2], resonant tunneling devices [3], Si/Ge nanopillars [4,5] and nanowires [6][7][8][9]. Continual technological innovations make it possible to create semiconductor structures with the MOS channel lengths in the order of 10 nm or even smaller.…”
mentioning
confidence: 99%
“…ble gate (DG) metal-oxide-semiconductor field effect transistors (MOSFET) [1,2], resonant tunneling devices [3], Si/Ge nanopillars [4,5] and nanowires [6][7][8][9]. Continual technological innovations make it possible to create semiconductor structures with the MOS channel lengths in the order of 10 nm or even smaller.…”
mentioning
confidence: 99%
“…Utilizing the second propagation in Equation set (2) and the orthogonality relations between the various R , A j χ allows one to rewrite Eq. (11) in matrix form,…”
Section: Generalized Eigenvalue Problem For Substrate Basementioning
confidence: 99%
“…The utilization of device physics concepts beyond tranditional CMOS will require the aid of computational tools capable of modelling the quantum transport of a finite number of electrons. A set of devices falling under this category are self-assembled Si/SiGe nanopillars, which utilize Si nanowires oxidized to a certain radius [1] and contain Ge rich cores [2], possibly displaying quantum dot behavior. Prediction of the electrical characteristics of such devices is cleary necessary but requires the development of a three-dimentional (3D), atomistic, full-band simulator.…”
Section: Introductionmentioning
confidence: 99%
“…In past years, silicon dioxide (SiO 2 ) was the most important passivation layer used in III-V MSM-PDs [7]. Various studies on thermal oxidation of SiGe alloys revealed a selective oxidation for silicon, which was accompanied by the rejection of Ge from the oxide and thus resulting in a Ge pile-up at the interface [8][9][10]. Furthermore, misfit dislocations would be generated during the high temperature oxidation process and strain relaxation would occur in the Si/SiGe heterostructure, thus degrading device performance.…”
Section: Introductionmentioning
confidence: 99%